Analisis Penggunaan Anggaran Remunerasi Sebagai Insentif Kinerja Tenaga Kependidikan - Erlizar Martiwi Hatmi; Teguh Wahyudi; Oki Muslahuddin; Riana Suprapto (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The issue of remuneration in State Universities as an award for employee performance achievements is expected to be a driver of superior performance. This study aims to describe the use of remuneration incentive budgets at the State University of Surabaya which has implemented a remuneration award system for 7 years. Presentation of remuneration data and data collection through surveys and in-depth interviews with remuneration policy makers and recipients of remuneration incentives. The results of the study indicate that the use of remuneration incentive budgets for education personnel is used more for the payment of routine activities for the duties and functions of education personnel, while for non-duties and functions it is still very low. Although it does not aim to prove the relationship between remuneration and performance, this study shows that the success of employees in achieving performance is still limited to quantity and does not state the quality of performance results.